2018
DOI: 10.1051/matecconf/201818804024
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment of tool steels against galling failure

Abstract: Abstract. In the present study two highly alloyed steel grades, intended for cold working applications, were subjected to plane-contact, nonlubricating sliding friction testing in order to estimate the working regions (applied pressure and sliding velocity) that are governed by mild, moderate and severe wear mechanisms, before and after nitrocarburizing. For this purpose, both tool steel grades were initially pre-subjected to the proper heat treatments, in order to achieve a final bulk hardness of 40, 50 and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 11 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…These models are mainly based on improved regression analysis [9]. However, the regression method is having a limitation as the structure of the model is based on only a limited number of linear or nonlinear equations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These models are mainly based on improved regression analysis [9]. However, the regression method is having a limitation as the structure of the model is based on only a limited number of linear or nonlinear equations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [19] concerning the comparative study of the same steel grades with and without surface nitrocarburizing surface treatment, it was demonstrated that Tufftriding prevents galling failure (Figure 8), i.e., motion suspension of a metal-metal tribopair due to strong adhesion phenomena having occurred at the contact surface during dry sliding, typically observed in the case of sliding bearings. Moreover, nitrocarburizing protects the metallic surface from extensive oxidation (Figure 9a) that can lead to secondary tribo-corrosion mechanisms that would increase the wear rate of the metallic component.…”
Section: Degradation Of Nitriding Layers and Acceleration Of Base Metmentioning
confidence: 96%
“…In most cases, the hidden layer performs a nonlinear transformation in order to capture the nonlinear behavior between the input and output variables of the considered problem [72][73][74][75]. In this study, the well-known sigmoid function was employed as the nonlinear transformation of the signal for a given neuron in the hidden layer as follows [76][77][78][79][80]:…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…given neuron in the hidden layer as follows [76][77][78][79][80] are the received signals coming from the previous neurons and y is the output signal of the considered neuron. In the output layer, a linear transformation function is applied to calculate the response of the prediction problem, which is the compressive strength of HPC in this study.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%